Cultural identity and the culture of globalization - bensalah, youssef; benayed, monia (Journal of Social Sciences and Humanities, 2021)
Cultural identity is one of the most controversial and controversial topics, as it includes many contents and is governed by a number of dimensions: such as religion, language and cultural heritage, especially with the great challenge it faces supported by powerful mechanisms and forces known as the phenomenon of globalization in light of the huge revolution in the field of communication and transportation, the transformation of Through which the world became a village and led to a direct link between Western and Arab countries and their interaction, subjectively and objectively. This study aims to identify the manifestations of globalization and the mechanisms of its impact on cultural identity, adopting the analytical approach based on theoretical studies of the subject of globalization, identity and culture.